Undergraduate Business Students’ Perceptions of Accounting Practices and Profession - Pečiūrienė, Aleksandra (Buhalterinės apskaitos teorija ir praktika, 2022)
Attraction of advanced students interested in studying at HEIs for an accounting major degree internationally remains a constant challenge to the accounting profession since the 1990s. To meet the demands it faces, the profession needs to be attractive for students who have the potential to become both technically competent professionals with good analytical abilities and communicative team players, able to understand the expanding business environment and think creatively. Unfortunately, there is a risk that potential students may possess false perceptions of accounting practices and profession. The aim of the research is to explore the perceptions of accounting of the students enrolled in the studies for non-accounting major degree of Professional Bachelor in Business Administration at Lithuanian HEIs. Foremost, the paper analyses the studied assessing approaches and tools used in the notable prior research on the topic. This is followed by the revealed methodology and analysed findings for the research carried out. One of the more important discovers was that the female students assessed the accounting significantly as more definite, boring, precise, and compliance driven than male students. Even considering the abovementioned differences, the results of the perception factors’ analysis strongly suggest that the surveyed students despite their gender in the mass hold traditional stereotypical perceptions of accounting. Due to sufficient number of the surveyed students, findings in overall are applicable to the target group of the research. Finally, the paper provides conclusions, limitations and insights for feasible further research in the study area.